ENGLISH ROMANTICISM AND ITS DEVELOPMENT: Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
England can be considered, to a certain extent, the ancestral home of romanticism. Early bourgeois development there also gave rise to the first anti-bourgeois aspirations, which later became characteristic of all romantics.